A contrastive analysis of idioms expressing optimism and pessimism in english and vietnamese - Đoàn Thị Uyên (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Idiom is one of complicated linguistic aspects as its meaning is unpredictable from its individual constituents. As the reseacher who is interested in discovering the figurative meaning of optimistic and pessimistic idioms, the researcher conducted this study. The two aspects of linguistics under investigation were semantic and syntactic features of English and Vietnamese idioms expressing optimism and pessimism. From the description, comparision and constrasting, similarities and differences between the idioms in both languages were identified. A combination of research methods was used for this thesis such as descriptive method, qualitative and quantitive method and constrastive analysis method. As for the data corpus, a total of 200 idioms in English and Vietnamese were gathered from reliable websites, poems and newspapers. Syntactically, idioms were found in both phrase structures and clause structures. Vietnamese idiomatic clauses occur in a higher frequency compared to English ones. Semantically, the field of optimism could be divided into seven subcatogories: hopefulness, confidence, encouragement, elation, gratitude, cheerfulness and enthusiasm. Likewise, pessimism consists of four subcatogies: hopelessness, melancholy, depression and negative expectation. The findings of this thesis have been employed as a foundation for the researcher to suggest some implications for the teaching and learning of idioms expressing optimism and pessimism.